Art as an investment in Poland: The first 20 years after the collapse of the central planning economy - Tomasz Potocki; Anna Rogozińska (e-Finanse: Financial Internet Quarterly, 2015)
The article aims at answering the following research question: is the Polish art market mature enough to look at art investment as an important element of portfolio diversification? To provide an answer, the Authors analyzed auctions in Poland from the period 1991-2010, which were published by Art&Business magazine. The number of the analyzed records amounted to 28951. The conclusions may be valuable for researchers specializing in art economics, investors dealing with wealth transfer, financial advisors offering financial products as well as for policy makers responsible for providing institutional infrastructure essential for development of the Polish art market.
Keywords: D14; Z11; G11; 330; art investment; art market; portfolio diversification; alternative investments; emotional investments; Poland